National exceptionalism in the 'EduCanada' brand: unpacking the ethics of internationalization marketing in Canada. Issue 3 (4th May 2018) - Stein, Sharon
ABSTRACT: Canada's recently revamped international education brand, EduCanada, offers a rich example of developments at the intersections of higher education internationalization and marketization. In this paper, I examine the EduCanada website to consider how national exceptionalist and 'othering' narratives are reproduced in the recruitment of international students. From these findings I ask how internationalization relates to the overlapping and ongoing legacies of Indigenous colonization, and racialized regimes of personhood, citizenship, and immigration in Canada. Finally, I argue that the international marketization of higher education risks foreclosing critical examinations of the entanglements of empire within which we are all unevenly embedded.